Activation of peripheral serotonin 5-HT1A and 5-HT1B/1D receptors contributes to the antinociceptive properties of metformin - Pecikoza, Uroš; Lasica, Andjelka; Tomić, Maja; Micov, Ana; Nastić, Katarina; Stepanović-Petrović, Radica (Archives of Pharmacy, 2022)
Several lines of (pre)clinical evidence have emerged that the antidiabetic drug metformin can alleviate inflammatory/neuropathic pain. Although the mechanism is not completely understood, there are reports that metformin can affect neurotransmitters involved in pain modulation, such as its ability to increase peripheral serotonin release. Here, we evaluated metformin’s efficacy following local peripheral administration in an inflammatory pain model and examined the potential involvement of serotonin receptors. We used the formalin test in mice, where we measured duration of nociceptive behavior in the first and second phase of the test. First, we examined the metformin’s antinociceptive effects following intraplantar administration. Additionally, the highest tested metformin dose was applied contralateral to the formalin-injected side, to exclude possible systemic effects. In the second part, we evaluated the effects of a 5-HT1A (WAY100635) and 5-HT1B/1D antagonist (GR127935) on the antinociceptive effects of a fixed, effective dose of metformin (antagonists were co-administered intraplantarly with metformin). Metformin (0.1-2 mg/paw) produced significant and dose-dependent antinociceptive effects (32-72%) in the second (inflammatory) phase. Contralateral application of metformin (2 mg/paw) had no significant antinociceptive effects. Both antagonists significantly reduced the antinociceptive effects of metformin (1 mg/paw). The levels of inhibition of metformin’s antinociceptive effect produced by WAY100635 were 56% (5 μg/paw) and 82% (7.5 μg/paw), whereas GR127935 inhibited metformin’s efficacy by 24% (3.75 μg/paw) and 80% (5 μg/paw). This study demonstrates that peripheral metformin application can produce antinociceptive effects against inflammatory pain and that activation of peripheral 5-HT1A and 5-HT1B/1D receptors contributes to these effects.